How Does Attention Alter Length Perception? A Prism Adaptation Study - Cai, Yong-Chun; Su, Xian; Yang, Yu-Mei; Pan, Yu; Zhu, Lian; Luo, Li-Juan (Frontiers in Psychology, 2020)
How perceived size (length) of an object is influenced by attention is in debate. Prism adaptation (PA), as a type of sensory motor adaptation, has been shown to affect performance on a variety of spatial tasks in both neglect patient and healthy individuals. It has been hypothesized that PA’s effects might be mediated by attentional mechanisms. In this study, we used PA to laterally shift spatial attention, and employed a precise psychophysical procedure to examine how the perceptual length of lines was influenced by this attentional shifting. Participants were presented with two separate lines in the left and right visual fields, and compared the length of the two lines. Forty-five healthy participants completed this line-length judgement task before and after a short period of adaptation to either left- (Experiment 1) or right-shifting (Experiment 2) prisms, or control goggles that did not shift the visual scene (Experiment 3). We found that participants initially tended to perceive the line presented in the left to be longer. This leftward bias of length perception was reduced by a short period of visuomotor adaptation to the left-deviating PA. However, for the right-shifting PA and plain glass goggles conditions, the initial length perception bias to the left line was unaffected. Mechanisms of this asymmetric effect of PA was discussed. Our results demonstrate that the length perception of a line can be influenced by a simple visuomotor adaptation, which might shift the spatial attention. This finding is consistent with the argument that attention can alter appearance.